'Mondragon': A clonal plum rootstock to enhance management of Armillaria root disease in peach orchards of Mexico. (July 2019) - Elias-Roman, Ruben Damian; Calderon-Zavala, Guillermo; Guzman-Mendoza, Rafael; Vallejo-Perez, Moises Roberto; Klopfenstein, Ned B.; Mora-Aguilera, Jose Antonio
Abstract: Root disease caused by Armillaria mexicana and/or A. mellea is associated with tree mortality in peach ( Prunus persica ) orchards within their primary production zone of the Mexican sub-tropics. To improve management options for this disease, the resistance/susceptibility reactions of three Prunus rootstocks to infection by A . mexicana (isolate MEX85) and A . mellea (isolate MEX100) were evaluated under greenhouse and field conditions. Greenhouse phase: A . mexicana and A . mellea were independently inoculated on 14 trees (10-month old) of each rootstock in polycarbonate containers: P . persica  ×  P. davidiana 'Nemaguard', P. persica landrace 'Criollos of La Goleta' genotypes, and P. salicina Japanese plum 'Mondragon'. Four non-inoculated trees of each rootstock were maintained as controls, and variables related to tree growth and disease incidence were monitored for all trees. At 22 months post-inoculation with A . mexicana in the greenhouse, 'Mondragon' showed the lowest (2.5%) incidence of infected roots (IRI), while 'Criollos of La Goleta' and 'Nemaguard' rootstocks showed the highest (21.6 and 24.6%, respectively) IRI. With greenhouse-grown plants inoculated with A . mexicana, the dry weights and volumes of roots, and dry weights of entire plants were greater (2.2–4.8 times higher) for 'Criollos of La Goleta'; however, abundant mycelia were observed within the root collar and lateral roots of this rootstock. In contrast, A . mellea inoculation resulted in relatively low (17.5%) incidence of root infection. In a commercial orchard (field phase) with high (35.3% symptomatic and dead trees) incidence of A . mexicana, 21 plants of 'Mondragon' (propagated via stem cuttings), 'Criollos of La Goleta', and P. mume 'Japanese apricot' were inoculated with the A . mexicana isolate. In the field, 'Mondragon' showed the lowest (1.0 disease severity at 66 months post-inoculation, P < 0.05) susceptibility to A . mexicana . No Armillaria infection was found on control plants; however, A . mexicana and A . mellea were re-isolated from inoculated plants to fulfill Koch's postulates. This work contributes to the development of efficient management strategies for Armillaria root disease in peach orchards in Mexico through the identification of 'Mondragon' as a rootstock with resistance to A . mexicana . Highlights: 'Mondragon', a new resistant rootstock to Armillaria for peach growers in Mexico. Armillaria mexicana was pathogenic in four Prunus rootstocks. Armillaria mexicana was more virulent than A. mellea . Mexican landrace of Prunus persica rootstocks were susceptible to Armillaria mexicana .